Analisis Hubungan Indeks Harga Saham Gabungan dan Exchange Rate terhadap Return Saham dengan Profitabilitas sebagai Variabel Intervening - Ni Luh Putu Desi Riadevi; Gede Sri Darma (Universitas Pendidikan Nasional, 2016)
Return and high profitability is the target to be achieved by all companies. Manythings affect the return of which is the stock price index and the exchange rate. This studyaims to determine the effect of stock price index and the exchange rate of Industry stockreturns on real estate and property in the Indonesian stock exchange with profitability as anintervening variable. The population in this study is 23 companies in the real estate andproperty industry listed on the Indonesia Stock Exchange during the period from 20,111 to2014 years. Testing the hypothesis of this study using the technique of path analysis (pathanalysis), with the application of tools Amos version 20. The results showed that: (1) thestock price index and exchange rate positive effect on returns and profitability also a positiveeffect on return. (2) The effect of stock price index and the exchange rate of the return isgreater than the direct effect of stock price index and the exchange rate to return throughprofitability. It is advisable in future studies to add variables that affect returns and alsoexpand the study sample so that the results could be better.Keywords: Stock Price Index, Exchange Rate and Stock Return,Profitability.